Pengaruh Motivasi terhadap Kinerja Karyawan dengan Employee Engagement sebagai Variabel Intervening di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Surakarta - Atala Cindy Fatya; Esti Dwi Rahmawati (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
The purpose of this study is to determine the influence of motivation on employee performance through employee engagement as an intervening variable in the Surakarta City Investment and One-Stop Integrated Services Office. The sampling method used saturated sampling with a total of 58 respondents. Data collection was carried out by distributing a questionnaire at the Surakarta DPMPTSP office. The analysis technique uses PLS (Partial Least Square) with the SmartPLS 3.0 program. The results of the study show that motivation has a positive and insignificant effect on employee performance, employee engagement has a positive and significant effect on employee performance, motivation has a positive and significant effect on employee engagement, and employee engagement can mediate the influence of motivation on employee performance.